2000
DOI: 10.1128/jb.182.3.637-646.2000
|View full text |Cite
|
Sign up to set email alerts
|

Surface Signaling in Ferric Citrate Transport Gene Induction: Interaction of the FecA, FecR, and FecI Regulatory Proteins

Abstract: In Escherichia coli, transcription of the ferric citrate transport genes fecABCDE is controlled by a novel signal transduction mechanism that starts at the cell surface. Binding of ferric citrate to the outer membrane protein FecA initiates a signal that is transmitted by FecR across the cytoplasmic membrane into the cytoplasm where FecI, the sigma factor, is activated. Interaction between the signaling proteins was demonstrated by utilizing two methods. In in vitro binding assays, FecR that was His tagged at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
111
1
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 26 publications
1
111
1
7
Order By: Relevance
“…6). It has been shown that in the Fec system, FecA and FecI both interact physically with FecR (46). Interactions between the protein components of the FpvA͞FpvR͞ PvdS pathway have not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…6). It has been shown that in the Fec system, FecA and FecI both interact physically with FecR (46). Interactions between the protein components of the FpvA͞FpvR͞ PvdS pathway have not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the N terminus abolishes induction, but transport is fully retained (28). FecR interacts with the FecI sigma factor in the cytoplasm and controls transcription initiation of the fec transport genes (18,43). Comparisons with genome sequences of other bacteria reveal homologs of FecIRA whose encoding genes are arranged in the same order as fecIRA of E. coli (7).…”
mentioning
confidence: 99%
“…Binding Assays Using Immobilized HrcA114 -To demonstrate interactions between HrcA and GroEL, we analyzed binding of GroEL to immobilized HrcA114 following the method described by Enz and coworkers (24). Two Ni-NTA-agarose columns were prepared, one loaded with His 6 -HrcA114 and the other left without protein.…”
Section: Bacterial Strains and Plasmids And Growthmentioning
confidence: 99%